Condition of Women and Children In India: Exploring the Evolution of Women's Status in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
All over the world woman has to play multifaceted rolesof a wife, daughter, sister, mother, administrator, a statesperson and manymore. Since the advent of civilization in India woman has been revered as agoddess ‘srajini’ given an equal platform ^^;= ukeZLrq iwT;Urs jeUrs r= nsork^^ Biological aweaker sex her status in India has been subject to many great changes. Throughgiven equal platform with her, she was subjected to discrimination andoppression based on class, caste and gender. From the beginning she has provedher position in every field and fulfilled the officers with great efficiencyRani Laxmi Bai, Razia Sultan who ruled India and glorified womanhood. AfterIndependence women also participated in active politics became president ofIndia Prime Minister and chief minister of states.